Ultrafast Charge Carrier Dynamics in Lead-Free Double-Perovskite Microcrystals - Mishra, Samita; Sapru, Shradha; De, Arijit K. (Optica Publishing Group, 2022)
Ultrafast electron and hole relaxation dynamics in microcrystals of a layered double-perovskite in two solvents is studied and found to proceed at different rates depending on the nature of charge carriers as well as solvents.
Only IISERM authors are available in the record
Keywords: Perovskite; Microcrystals